Study protocol for a zinc intervention in the elderly for prevention of pneumonia, a randomized, placebo-controlled, double-blind clinical pilot trial - Ortega, Edwin F.; Wu, Dayong; Guo, Weimin; Meydani, Simin Nikbin; Panda, Alexander (Frontiers in Nutrition, 2024)
Pneumonia is a major public health problem for older adults, being one of the leading causes of hospitalization and death, particularly for elderly nursing home residents. We previously conducted a clinical trial in which we demonstrated that 29% of nursing home residents had low serum zinc levels coinciding with a two-fold increase in pneumonia incidence and duration in comparison to individuals with adequate serum zinc levels. However, causality could not be inferred and necessitates a double-blind clinical trial. To determine the appropriate supplementation dose for such a trial we are conducting a randomized, placebo-controlled, double-blind clinical pilot trial aimed at delineating the optimal dosage (30 and 60 mg/day elemental Zn) and establishing safety. The results from the pilot study will be leveraged to inform our larger randomized clinical trial designed to study the effect of zinc supplementation in nursing home elderly with low serum zinc levels on respiratory infections, antibiotic use, and duration of sick days with pneumonia. In tandem with dose optimization, we will evaluate the correlation between serum zinc and pan-T cell zinc levels, given that T cells and their zinc levels are important in the response and resolution of respiratory infections but whose correlation has only been extrapolated and not demonstrated. Herein we present the study rationale and protocol, as well as discuss specific challenges we encountered in securing a manufacturer for the study agents and when recruiting from nursing home populations during the COVID-19 pandemic. In light of these experiences, we provide recommendations for future clinical trials under circumstances where supply chains are disrupted, and recruitment pools are constrained or unavailable.